ANALYSIS OF EARLY MARRIAGE AND EDUCATIONAL BACKGROUND (CASE STUDY IN KP. CIATEUL LABUAN VILLAGE – PANDEGLANG) - Mustakim, Usep Saepul; Muliasari, Ajeng; Sulaeman, Yeni; Munawar, Badri; Dewi, Ratna; Nurdiana, Septi; Yani, Inda; saminah, Mimin (LPPM Institut Pendidikan Nusantara Global, 2023)
Looking from the background above, the problem problem that will be addressed in this study is: 1) how the problem descriptions of married by accident persons in the early marriage of youth in the Ciateul village labuan 2) how can nalisis result from the problem of married by accident people in the ciateul village. The objective of the study is to analyze the factor that causes a youth to get married early in the Ciateul Village Researchers use observation and interview methods by viewing and then locating the problem at hand to obtain data relating to an analysis of existing writing. A premature marriage not only brings negative but also positive effects, such as the benefit of those who have avoided promiscuity because of past history of pregnancy and in the economic sense of premature marriage. Because when it comes to having children, it's only when children need expenses that parents have the strength to make ends meet. Further negative effects are the result of premature marriage in the Ciateul Labuan also varies, such as getting bad labels from people, and then two miscarried research informants, an economic downturn and a psychological breakdown.